2008
DOI: 10.1016/j.jdent.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of brackets using a caries-protective adhesive patch

Abstract: OBJECTIVES: The purpose of this study was to assess the shear bond strength (SBS) of metal brackets when placed with a caries protective adhesive patch. METHODS: Forty stainless steel brackets (Ormco) were bonded to 40 bovine enamel samples according to the following conditioning/bonding procedures using a resin-based orthodontic luting material (Heliosit Orthodontic, N=10 per group): (A) 35% phosphoric acid (30s), rinse and dry; (B) as in A but additional placement of a prototype adhesive patch (Ivoclar Vivad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
1
18
0
2
Order By: Relevance
“…30,31 In spite of using fluoride and glass ionomer particles in composite restorations, it seems using composite resin cements containing antibacterial materials would be useful for reducing caries activity around orthodontic brackets. 8,32,33 Failure of posterior class II composite restorations due to microleakage and secondary caries can be prevented by using these bactericidal composites as liners under final restorations.…”
Section: Jcdpmentioning
confidence: 99%
“…30,31 In spite of using fluoride and glass ionomer particles in composite restorations, it seems using composite resin cements containing antibacterial materials would be useful for reducing caries activity around orthodontic brackets. 8,32,33 Failure of posterior class II composite restorations due to microleakage and secondary caries can be prevented by using these bactericidal composites as liners under final restorations.…”
Section: Jcdpmentioning
confidence: 99%
“…2,6 Prevention methods mainly target the remineralization process and the inhibition of present bacterial flora through topical fluoride applications, use of adhesives with remineralization potential that contains amorphous calcium phosphate or fluoride, casein phosphopeptide-amorphous calcium-phosphate-containing pastes, chlorhexidine mouth rinses, ozone applications, probiotics, xylitol, and sealants. 2,6,7 Although remineralization of WSL could be achieved to some extent using related measures, clinically it has been shown that WSL do not disappear unless they are removed mechanically by abrasion, etching, or masking by resin infiltration or treated in a restorative fashion. 8,9 Among these, prevention measures that do not require patient compliance are considered to be more predictable since only 13% of the patients were reported to achieve excellent cooperation with the use of mouth rinses and tooth brushing.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 Therefore, sealing the susceptible enamel prior to bracket bonding in order to form a caries-protective shield has been the focus of interest in previous studies that primarily intend to eliminate patient compliance. 7,11 In principle, sealants cover the whole buccal surface adjacent to brackets, forming a physical barrier. 2,7,11 This protective shield is subjected to physical challenges such as acid attacks from bacterial plaque and acidic soft drinks as well as daily tooth brushing, which might impair the seal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Despite recent advances in orthodontic materials and techniques, enamel decalcification and white spot lesion formation continue to pose problems for patients treated with fixed orthodontic appliances. 4,5 Decalcification is detected more commonly on the buccal surfaces of orthodontically treated teeth than on the other surfaces of the same teeth. 6 In these cases, to eliminate and/or minimize the caries risk, preventive efforts should concentrate on the direct suppression of cariogenic microflora by chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%